QUALITY STATISTICAL EVALUATION OF BAKERY FUNCTIONAL PRODUCTS FROM DIFFERENT CEREALS FLOURS MIXTURES, WITH A HIGH CONTENT OF β-GLUCANS - Nicolae-Ciprian POPA; Radiana-Maria TAMBA-BEREHOIU; Vasilica SIMION; Luminita VISAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of this research was the statistical evaluation of the effect of fibers rich flours addition, namely oat, barley and millet flours, in wheat flour (15% and 30%), on the dough technological parameters, as well as on the main bread quality parameters. In this regard, there have been analyzed: flours technological water absorption, dough pH after kneading, pH after fermentation, temperature after kneading, temperature after fermentation. The quality bread analyzes were: pH, moisture, porosity and volume. The results showed that water absorption increase extremely significant in oat and barley (30%) bread. Temperatures after kneading increased, especially in millet bread. Kneading and fermentation determined significant decreases of fibers rich dough pH. The Spearman correlation between the dough technological parameters (n=7) showed that the temperature after kneading correlated negative significant with pH after kneading (r=-0.821*). An extremely significant positive correlation has been established between dough pH after kneading and dough pH after fermentation (r=0.955***). Water absorption influenced bread moisture by 49% (r2=0.49). Bread with 30% millet flour, showed a significant increased porosity, against wheat bread (t=3,531*). The increase of water absorption decreased the porosity by 44% (r2=0.44) and the increase of temperature after kneading influenced the porosity increase by 51%. Flours pH (r2=0.41) and bread moisture (r2=0.41) influenced most bread pH. Bread volume did not correlate with any parameter. Functional bakery products with added fibers and increased content of vitamins, proteins and minerals, from oat, barley, and millet, help to maintain the consumers health.